Strategy Analysis of Seamlessly Resolving Turbulent Flow Simulations - Stefan Heinz (Aerospace, 2025)
Modeling of wall-bounded turbulent flows, in particular the hybridization of the Reynolds-averaged Navier-Stokes (RANS) and large eddy simulation (LES) methods, has faced serious questions for decades. Specifically, there is continuous research of how usually applied methods such as detached eddy simulation (DES) and wall-modeled LES (WMLES) can be made more successful in regard to complex, high-Reynolds-number (<semantics>Re</semantics>) flow simulations. The simple question is how it is possible to enable reliable and cost-efficient predictions of high-<semantics>Re</semantics> wall-bounded turbulent flows in particular under conditions where data for validation are unavailable. This paper presents a strict analysis of strategies for the design of seamlessly resolving turbulent flow simulations for a wide class of turbulence models. The essential conclusions obtained are the following ones: First, by construction, usually applied methods like DES are incapable of systematically spanning the range from modeled to resolved flow simulations, which implies significant disadvantages. Second, a strict solution for this problem is given by novel continuous eddy simulation (CES) methods, which perform very well. Third, the design of a computational simplification of CES that still outperforms DES appears to be very promising.